2017
DOI: 10.1007/s00784-017-2312-y
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of accuracy in implant site preparation performed in single- or multi-step drilling procedures

Abstract: Single-step preparations are less invasive and are promoting osseointegration. Even highly experienced surgeons are achieving higher levels of accuracy by combining this technique with template guidance. Hereby template guidance enables a reduction of hands-on time and side effects during surgery and lead to a more predictable clinical diameter.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 49 publications
1
16
0
Order By: Relevance
“…Therefore, as per earlier studies, inexperienced clinicians may benefit from FG implant placement [12][13][14]. For example, Rungcharassaeng et al found that the FG protocol reduced differences between experienced and inexperienced operators for placing single posterior implants no difference between experienced and inexperienced operators when FG protocol guides were used, while the differences became obvious when implants were placed without surgical guides [13,14]. According to Schulz et al, in the hand of final-year dental students, FG implant placement was more accurate than PG implant placement [15].…”
Section: Discussionmentioning
confidence: 80%
See 4 more Smart Citations
“…Therefore, as per earlier studies, inexperienced clinicians may benefit from FG implant placement [12][13][14]. For example, Rungcharassaeng et al found that the FG protocol reduced differences between experienced and inexperienced operators for placing single posterior implants no difference between experienced and inexperienced operators when FG protocol guides were used, while the differences became obvious when implants were placed without surgical guides [13,14]. According to Schulz et al, in the hand of final-year dental students, FG implant placement was more accurate than PG implant placement [15].…”
Section: Discussionmentioning
confidence: 80%
“…However, this hypothesis cannot be accepted for the PG and FH protocols as the anterior implants were generally more accurate than the posterior implants. Therefore, as per earlier studies, inexperienced clinicians may benefit from FG implant placement [12][13][14]. For example, Rungcharassaeng et al found that the FG protocol reduced differences between experienced and inexperienced operators for placing single posterior implants no difference between experienced and inexperienced operators when FG protocol guides were used, while the differences became obvious when implants were placed without surgical guides [13,14].…”
Section: Discussionmentioning
confidence: 84%
See 3 more Smart Citations